2021
DOI: 10.1002/dev.22179
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographics and chronic stress in mother–toddler dyads living in poverty

Abstract: Experiencing chronic stress early in life is associated with later health disparities, and poverty may be a significant stressor for both mothers and children. With a sample of primarily Black and White mothers (N = 75) and toddlers (N = 71) living in poverty in the United States, we examined the direct relations between sociodemographic conditions of poverty and chronic physiological stress. Mothers completed questionnaires on sociodemographics, including mother/toddler race, mother's education, father's educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Findings on the association between parental stress scores and other factors, such as mothers' education, were also observed, although not consistent across the study sites. These ndings have also been observed in a study of sociodemographic predictors of chronic stress in mothers [21]. Studies have suggested improved parenting practices through engagement programs among mothers with low educational levels, thereby promoting children's developmental outcomes [47].…”
Section: Insert Figurementioning
confidence: 62%
“…Findings on the association between parental stress scores and other factors, such as mothers' education, were also observed, although not consistent across the study sites. These ndings have also been observed in a study of sociodemographic predictors of chronic stress in mothers [21]. Studies have suggested improved parenting practices through engagement programs among mothers with low educational levels, thereby promoting children's developmental outcomes [47].…”
Section: Insert Figurementioning
confidence: 62%
“…Unmeasured variables may also account for our findings. For example, due to the nonexperimental and observational design of our study, other unmeasured variables (e.g., marital or cohabitation status, marital quality, number of individuals living in the household, receiving psychotherapy, or counseling) may have affected our results in this sample of many women with low‐income (e.g., Bates et al, 2021). ECEs' stressors also extend beyond our measured variables, particularly related to their workplace.…”
Section: Discussionmentioning
confidence: 99%
“…As hair grows approximately 1 cm each month (Loussouarn et al, 2016), it absorbs cortisol from the follicular bloodstream and thus can reflect the average serum cortisol concentration over the prior month (Russell et al, 2012). Bates et al (2021) found that chronic cortisol levels (mean hair cortisol concentration [HCC] analyzed with immunoassay) in a sample of mothers living in poverty in the Midwest ( n = 75; mean age 28.7 years) was 6.18 pg/mg (SD = 7.04; range 0.10–31.26). Serwinski et al (2016) found a mean chronic cortisol level (HCC analyzed with liquid chromatography‐mass spectrometry) in a sample of working women in London and Budapest ( n = 164; mean age 43.6 years, SD = 9.8) of 8.39 pg/mg (SD = 6.3).…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally, one study found that female caregivers reported that male caregivers' involvement in parenting reduced the stressors that come with parenting (Okelo et al, 2022). Such ndings have also been evident in other contexts; a study in the USA among mothers in low-income settings (Bates et al, 2021). For mothers in low-income settings, marriage could be a great contributor to an improved household nancial base, emotional support and support in taking care of the child(ren) (Wilcox et al, 2011).…”
mentioning
confidence: 92%